When Do Employees Become Entrepreneurs? - Hellmann, Thomas (Management Science, 2007)
This paper examines an economic theory of when employees become entrepreneurs. It jointly addresses the two fundamental questions of when employees generate innovations, and whether these innovations are developed as internal ventures or outside the firm. The model shows that if generating innovations distracts employees from their assigned tasks, firms may discourage innovation. Firms may reject profitable opportunities that fall outside of their core activities. If employees own the intellectual property (IP), they may leave to do a start-up. The allocation of IP rights also affects the generation of innovation. The external entrepreneurial environment is a complement to firm-internal innovation. If the external environment is particularly good, firms may embrace employee innovation and take advantage of it through spin-offs.